I Like You When I Know You Attitudinal Barriers to Responsive Vocational Education for Handicapped Students. "It Isn't Easy Being Special." Research & Development Series No. 174 - Brant, Lynn.; Ohio State Univ., Columbus. National Center for Research in Vocational Education ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1979)
This publication identifies common attitudes toward handicapped persons and provides suggestions for improving attitudes. The first of three major sections presents an historical review of pertinent legislation for education of the handicapped. Section 2 gives a brief review of what the legislation means for vocational education. The final section expounds upon the attitudes of educators, peers, parents, and the community. In addition, suggestions for improving attitudes within each group are given. (LRA)
Availability: National Center Publications, National Center for Research in Vocational Education, The Ohio State University, 1960 Kenny Road, Columbus, OH 43210 ($1.90; six-piece set, $25.00).
Sponsoring Agency: Office of Education (DHEW), Washington, DC.
ERIC Note: For related documents see CE 023 944-947 and CE 023 952.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Attitudes toward Disabilities; Community Attitudes; Counselor Attitudes; Educational Attitudes; Educational Legislation; Handicapped Students; Mainstreaming; Parent Attitudes; Peer Influence; Student Attitudes; Teacher Attitudes; Vocational Education; Information Analyses; Guides, Non-Classroom.